Uji Efektivitas Anthelmintik Formula Suspensi Biji Mentimun (Cucumissativus L.) Terhadap Cacing Gelang (Ascaris Lumbricoides) : The effectiveness Test of Cucumber Seeds Suspension Formula (Cucumissativus L.) Towards Roundworms (Ascaris Lumbricoides) as Anthelmintic - Farid, Nurfiddin; Syamsu, Andi Suparlan Isya; Aliah, Ahmad Irsyad; Murdi, Anna Muthmainna (Universitas Tadulako, 2020)
The Effectiveness Test of Cucumber Seeds Suspension Formula (Cucumis sativus L) towards Roundworms (Ascaris lumbricoides) as in Vitro Anthelmintic, It has been conducted research to know cucumber seeds powder (Cucumis sativus L) can be made into form of suspension stock and to know stock of cucumber seeds suspension (Cucumis sativus L) can give effect of anthelmintic toward roundwoms Ascaris lumbricoides. The research was conducted by using experimental method. Powder of cucumber seeds (Cucumis sativus L) were made into suspension stock with 3 concentratios such as 5%, 10%, 15% concetrations and suspension without powder of cucumber seeds (Cucumis sativus L) with different addition subtance concentration. Test animal used was roundworm (Ascaris lumbricoides) that was taken by pigâ€™s intestine. Treatment group consisted into five categories such as 125 mg positive control of pamoat pirantel (CombantrinÂ®), negative control of suspension without powder of cucumber seeds (Cucumis sativus L), and category of cucumber seeds suspension (Cucumis sativus.L) as 5%, 10%, and 15%. Each group was soaked with 40 ml test ingredient into petri dish. Then it was observed and writte the number of died worms in every minute. 100% observation of died worm was group of positive control at 405 minutes, negative control at 1710 minutes, 5% concetration of cucumber seeds suspension stock at 540 minutes, 10%concentration at 465 minutes and 15% concentration at 420 minutes. The result of research showed that cucumber seeds (Cucumis sativus L) can be made into suspension stock and effective as anhelmintic toward roundworms Ascaris lumbricoides.